Percepção de professores (as) sobre as condições de acessibilidade em academias - SANTOS, Rayssa Marise da Costa dos (2022)
This study aimed to analyze the perception of Physical Education teachers about the accessibility conditions of academies in Belém do Pará to assist people with physical disabilities. With a quantitative-qualitative approach, the research investigated 26 teachers working in 10 academies located in Belém, using the form filled out online. We observe that training and professional work directly and indirectly exert a significant impact on the provision of adapted and quality activities and services to the public with disabilities, especially the physically challenged. The structuring of gyms in terms of accessibility conditions proves to be a relevant factor for the access, permanence and free movement of people with physical disabilities in their interior. The standards of the Brazilian Association of Technical Standards (ABNT) are presented, in this context, as important allies to such purposes. In the eyes of most professors, the academies are adequate in terms of accessibility standards. Despite this, however, some of them still need to be better structured in order to guarantee the right of free movement and participation in practices with countless benefits for people with physical disabilities.